Relationships between body image, dyadic coping and post-traumatic growth in breast cancer patients: a cross-sectional study - Wang, Yuan; Wang, Shan; Tong, Ling; Zhuang, Jiaru; Xu, Yihan; Wu, Yibo; Chen, Ling (Frontiers in Psychology, 2024)
Background: The diagnosis and treatment of cancer triggers not only a negative psychological response for the patient, but also a positive psychological outcome. Positive dyadic coping, as a form of coping for mental health outcomes, can maintain or reestablish internal stability between the patient and his or her spouse, resulting in positive physical and psychological changes. However, there is a paucity of research on body image, dyadic coping, and post-traumatic growth in breast cancer patients. The purpose of this study was to explore the relationship and pathways between body image, dyadic coping, and post-traumatic growth (PTG) in breast cancer patients. Methods: A cross-sectional study was conducted from November 2022 to November 2023 at a tertiary care hospital in Wuxi, Jiangsu, China. This study was conducted among 154 breast cancer patients treated at the Affiliated Hospital of Jiangnan University, all of whom completed demographic and clinical information questionnaires, Body image self-rating questionnaire for breast cancer (BISQ-BC), Dyadic Coping Inventory (DCI) and Post Traumatic Growth Inventory (PTGI). A Pearson correlation analysis was used to explore the relationship between body image, dyadic coping, and post-traumatic growth. Structural equation modeling was used to analyze the path relationships among the three and to explore the mediating role of dyadic coping. Results: Body image were negatively correlated with post-traumatic growth (r = -0.462, p < 0.01); Body image was negatively correlated with dyadic coping (r = -0.308, p < 0.01); And dyadic coping was positively associated with post-traumatic growth (r = 0.464, p < 0.01); The structural equation modeling results supported the mediation model with the following model fit indices, chi-square to degrees of freedom ratio (χ2/df=2.05), goodness of fit index (GFI=0.93), comparative fit index (CFI=0.99), canonical fit index (NFI=0.93), incremental fit index (IFI=0.99), non-canonical fit index (TLI=0.99) and the root mean square of the difference in approximation error (RMSEA=0.03). Body image and dyadic coping directly affected post-traumatic growth (β= -0.33, p<0.05; β= 0.43, p<0.05); And body image indirectly influenced post-traumatic growth through dyadic coping (β=-0.17, p<0.05). Conclusion: Interconnections between body image, dyadic coping, and post-traumatic growth in breast cancer patients.